Evaluation of Postoperative Cardiac Function in Severe Ischemic Heart Disease Associated with Decreased Ejection Fraction - Naitoh, Kouzou; Norita, Hiroaki; Itoh, Tsuyoshi; Natsuaki, Masafumi; Suda, Hisao (Japanese Journal of Cardiovascular Surgery, 1997)
This clinical study was peformed to clarify the postoperative cardiac functions after coronary artery bypass graft surgery in the cases associated with decreased left ventricular ejection fraction (EF) or increased end-diastolic volume index (EDVI). The patients were divided into two groups by preoperative EF. The EF of Group I ranged from 31 to 39% in 42 cases, and the EF of Group II was below 30% in 27 cases. Several parameters of cardiac function such as EF, peak ejection rate (PER), peak filling rate (PFR) or early diastolic peak filling rate were evaluated with radionuclide ventriculography. Postoperative mean values of these parameters significantly improved in both Group I and Group II compared to preoperative values. Although these parameters and left ventricular wall motion did not improve in the 7 cases with an EDVI over 140ml/m2 in Group II, the clinical results of these 7 cases were good during the follow-up period except one case which preoperatively had frequent ventricular arrythmia. The clinical condition improved remarkably in the 3 patients who had preoperative angina pectoris among these 7 cases. Surgical indications must be carefully determined in cases with increased EDVI and frequent ventricular arrythmia.